2017
DOI: 10.1515/amm-2017-0230
|View full text |Cite
|
Sign up to set email alerts
|

High Versatility of Niobium Alloyed AHSS

Abstract: The effect of processing parameters on the final microstructure and properties of advanced high strength CMnSiNb steel was investigated. Several processing strategies with various numbers of deformation steps and various cooling schedules were carried out, namely heat treatment without deformation, conventional quenching and TRIP steel processing with bainitic hold or continuous cooling. Obtained multiphase microstructures consisted of the mixture of ferrite, bainite, retained austenite and M-A constituent. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Therefore, industrial requirements prefer low-Si grades in TRIP-aided steels [16,17]. The decrease of the solid solution potential of silicon and a resulting decrease of the strength level (Al has a smaller solid solution strengthening effect) can be compensated by Nb, Ti, and/or V microalloyed additions [18][19][20][21][22]. These elements form stable nitrides and carbonitrides during hot working in the austenite region.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, industrial requirements prefer low-Si grades in TRIP-aided steels [16,17]. The decrease of the solid solution potential of silicon and a resulting decrease of the strength level (Al has a smaller solid solution strengthening effect) can be compensated by Nb, Ti, and/or V microalloyed additions [18][19][20][21][22]. These elements form stable nitrides and carbonitrides during hot working in the austenite region.…”
Section: Introductionmentioning
confidence: 99%
“…When the Newton-Raphson method is introduced to obtain a proper numerical approximation, it is normal to set the initial value of ∆γ to 0. To improve convergence, however, ∆γ (0) is defined as shown in Equation (28).…”
Section: Modification Of the Damage Modelmentioning
confidence: 99%
“…Moreover, one should note that the rapid degradation represented by a necking-failure phenomena occurred immediately after reaching the tensile strength. Earlier studies reported that microstructural effects such as martensite formation and mechanical twinning contributed to the strengthening of high manganese steel and delayed the onset of necking, which is associated with large uniform elongation [24][25][26][27][28][29]. Based on these features, strength-based design is typically performed for industrial structures and can lead to structural safety problems with respect to excessive deformation and rapid necking-fracture in high manganese steel.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of retained austenite is due to its high thermal stability revealing during heat treatment. Its stability is influenced by carbon and manganese contents in the austenite, a morphology, dislocation density and the neighborhood of soft or hard phases [7][8][9]. These factors determine the amount of retained austenite present in the microstructure and resulting mechanical properties.…”
Section: Introductionmentioning
confidence: 99%